Geomorphic Controls on Landslide Activity in Champlain Sea Clays along Green’s Creek, Eastern Ontario, Canada - Hugenholtz, Chris; Lacelle, Denis (Géographie physique et Quaternaire, 2004)
AbstractLandslides in Champlain Sea clays have played an important role in shaping Eastern Ontario’s landscape. Despite extensive research, there is a limited understanding of the relations between landslide activity, climatic controls, and the geomorphic evolution of river valleys in Champlain Sea clay deposits. With these issues in mind, a study was undertaken to determine the controls on the spatio-temporal distribution of contemporary landslide activity in valley slopes composed of Champlain Sea clay. The study area was the Green’s Creek valley located in the east end of Ottawa, Ontario. Observations and measurements indicate that landslide activity is closely related to valley development. An inventory of landslide activity from 73 years of aerial photographs revealed that landslides occurred preferentially in slopes located on the outside of meander bends, and that they often recurred in the same slope after a period of ripening. The largest and highest density of landslides occurred along a major tributary valley where geomorphic features such as knickpoints, V-shaped valley profiles and bedrock depth-to-slope height ratios reflect an unstable phase of valley development. A small number of landslides incurred successive failures along the slopes of the backscarp for several years-to-decades after the initial failure. Correlation analysis showed that the temporal distribution of landslide activity has fluctuated in response to decadal-scale changes in the amount of precipitation.